Pediatric melanoma: Analysis of an international registry. Issue 22 (10th September 2013) - Averbook, Bruce J.; Lee, Sandra J.; Delman, Keith A.; Gow, Kenneth W.; Zager, Jonathan S.; Sondak, Vernon K.; Messina, Jane L.; Sabel, Michael S.; Pittelkow, Mark R.; Ecker, Phillip M.; Markovic, Svetomir N.; Swetter, Susan M.; et al.
Abstract : BACKGROUND: The management of pediatric melanoma (PM) has largely been extrapolated from adult data. However, the behavior of PM appears to differ from its adult counterparts. Therefore, an international PM registry was created and analyzed. METHODS: Twelve institutions contributed deidentified clinicopathologic and outcome data for patients diagnosed with PM from 1953 through 2008. RESULTS: Overall survival (OS) data were reported for 365 patients with invasive PM who had adequate follow‐up data. The mean age of the patients was 16 years (range 1 year‐21 years). The 10‐year OS rate, 80.6%, tended to vary by patient age: 100% for those aged birth to 10 years, 69.7% for those aged > 10 years to 15 years, and 79.5% for those aged > 15 years to 20 years ( P  = .147). Patients with melanomas measuring ≤ 1 mm had a favorable prognosis (10‐year OS rate of 97%), whereas survival was lower but similar for patients with melanomas measuring > 1 mm to 2 mm, > 2 mm to 4 mm, and > 4 mm (70%, 78%, and 80%, respectively; P  = .0077). Ulceration and lymph node metastasis were found to be correlated with worse survival ( P  = .022 and P  = .017, respectively). The 10‐year OS rate was 94.1% for patients with American Joint Committee on Cancer stage I disease, 79.6% for those with stage II disease, and 77.1% for patients with stage III disease ( P  < .001). CONCLUSIONS: Tumor thickness, ulceration, lymph node status, and stage were found to be significant predictors of survival in patients with PM, similar to adult melanoma. There is a trend toward increased survival in children aged ≤ 10 years versus adolescents aged > 10 years. Further analyses are needed to probe for potential biological and behavioral differences in pediatric versus adult melanoma. Cancer 2013 ;119:4012–4019. © 2013 American Cancer Society . Abstract : In an international, multicenter, pediatric melanoma registry, tumor thickness, ulceration, lymph node status, and patient age were found to be significant predictors of survival, similar to adult melanoma. There was a trend toward increased survival in children aged ≤ 10 years compared with adolescents aged > 10 years. Additional analyses are warranted to examine the potential biological and behavioral differences in pediatric versus adult melanoma.